Glycated apolipoprotein B decreases after bariatric surgery in people with and without diabetes: A potential contribution to reduction in cardiovascular risk. (April 2022) - Iqbal, Zohaib; Bashir, Bilal; Adam, Safwaan; Ho, Jan H.; Dhage, Shaishav; Azmi, Shazli; Ferdousi, Maryam; Yusuf, Zahid; Donn, Rachelle; Malik, Rayaz A.; Syed, Akheel; Ammori, Basil J.; et al.
Abstract: Background and aims: The causal relationship between LDL cholesterol (LDL-C) and the pathogenesis of atherosclerosis is well established. Previous studies have shown that modifications, glycation and oxidation of LDL enhance its atherogenic potential. Glycation of LDL occurs in it is main protein component, apolipoprotein B100 (ApoB). Our aim was to assess the effect of bariatric surgery on circulating glycApoB levels and understand the factors influencing changes in its circulating levels. Methods: We measured glycApoB in 49 individuals before, 6 and 12 months after bariatric surgery. We also assessed clinical parameters, lipoproteins, markers of inflammation and glycaemia. Correlation analysis was done to understand associations between changes in variables from baseline to 12 months after surgery. Results: Reductions in glycApoB post-bariatric surgery were significant regardless of whether the patients suffered from type 2 diabetes (T2DM) or took lipid-lowering therapy. There were no significant differences in glycApoB levels at baseline and follow-up between participants with T2DM and those without. GlycApoB declined from baseline in non-diabetics at 6 months and significantly at 12 months (1.09 mg/l vs 0.63 mg/l vs 0.49 mg/l, p  < 0.05), and in those with T2DM at 6 months and significantly at 12 months (1.77 mg/l vs 1.03 mg/l vs 0.68 mg/l, p  < 0.05). The percentage change in glycApoB correlated ( p  < 0.05) with changes in glucose ( ρ  = 0.40), insulin ( ρ  = 0.41) and HOMA-IR (%) ( ρ  = 0.43). There were no significant associations between changes in glycApoB and changes in total serum ApoB, LDL-C, high sensitivity C-reactive protein, weight, or BMI. Conclusions: Bariatric surgery reduces levels of glycApoB; this reduction is associated with decreased insulin resistance postoperatively. This potentially reflects the potent influence of obesity-related insulin resistance on lipoprotein glycation. Our observations are of potential importance in explaining the effectiveness of bariatric surgery in decreasing cardiovascular disease (CVD) risk in both T2DM and obese individuals without T2DM, as glycation of ApoB is known to be associated with increased atherogenesis. Graphical abstract: Image 1 Highlights: Glycation is a non-enzymatic post secretory atherogenic modification of apolipoprotein B. Bariatric surgery reduces the levels of circulating glycApo B without changes in total apolipoprotein B. Changes in glycApo B correlated with changes in glycaemic parameters in individuals with diabetes. Our data are of importance in explaining the effectiveness of bariatric surgery in decreasing ASCVD risk.